2003
DOI: 10.1038/sj.bjp.0705434
|View full text |Cite
|
Sign up to set email alerts
|

Potent analgesic effects of anticonvulsants on peripheral thermal nociception in rats

Abstract: 1 Anticonvulsant agents are commonly used to treat neuropathic pain conditions because of their effects on voltage-and ligand-gated channels in central pain pathways. However, their interaction with ion channels in peripheral pain pathways is poorly understood. Therefore, we studied the potential analgesic effects of commonly used anticonvulsant agents in peripheral nociception. 2 We injected anticonvulsants intradermally into peripheral receptive fields of sensory neurons in the hindpaws of adult rats, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 29 publications
3
34
0
1
Order By: Relevance
“…Recently, some authors demonstrated that carbamazepine injected intraplantarly into the rat hind paw is a potent analgesic against acute thermal nociception in rats (11). The doses of carbamazepine they used were 3,000 -6,000 times lower than the commonly used doses of lidocaine (1% -2% solution or 1 -2 mg/ 0.1 ml), a well known and widely used local anesthetic.…”
mentioning
confidence: 99%
“…Recently, some authors demonstrated that carbamazepine injected intraplantarly into the rat hind paw is a potent analgesic against acute thermal nociception in rats (11). The doses of carbamazepine they used were 3,000 -6,000 times lower than the commonly used doses of lidocaine (1% -2% solution or 1 -2 mg/ 0.1 ml), a well known and widely used local anesthetic.…”
mentioning
confidence: 99%
“…Price et al showed that direct injection of NPW-23 into the hypothalamus influenced the excitability of specific groups of neurons in rats (17,18). In short, NPW has been shown to be a multifunctional endogenous ligand for NPBW 1 (19). In this work, we tested the hypothesis that, based on its analgesic properties, NPW may also suppress seizures when delivered into the brain.…”
mentioning
confidence: 95%
“…We hypothesize that the observed anticonvulsant effects exerted by hNPW-23, and the modified NPW analogues, resulted from activation of the NPBW 1 receptor which may result in hyperpolarization of the cell membrane. Hyperpolarization of the membrane would then result in decreased excitatory behavior of the neuron, thus modulating seizure activity (1,17). This hypothesis remains to be tested, and it is acknowledged that further studies into the precise mechanism by which NPW inhibits neuronal hyperexcitability need to be conducted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anticonvulsant agents have been used in pain management over the last few decades due to the clinical impression that they are effective in alleviating certain forms of pain for example neuropathic pain especially lancinating and burning pain (Todorovic et al, 2003), cancer pain (Keskinbora et al, 2007). Gabapentin has attracted recent attention because of its effectiveness against neuropathic pain in both controlled clinical trials and animal models (Kayser and Christensen, 2000).…”
Section: Anti-epileptics (Anticonvulsants)mentioning
confidence: 99%